Between Past and Future - 1/25
Oxford Scholar Timothy Garton Ash and President of the Republic of Hungary Árpád Göncz offer the closing remarks for a three days long international conference entitled "Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" hosted by CEU in March 1999. The video contains the second part of Timothy Garton Ash's concluding remarks delivered in the CEU Auditorium.